Numerical study of pebble recirculation in a two-dimensional pebble bed of stationary atmosphere using LB-IB-DEM coupled method. (February 2019) - Gui, Nan; Li, Zeguang; Zhang, Zhen; Yang, Xingtuan; Tu, Jiyuan; Jiang, Shengyao
Highlights: LB-IB-DEM simulation of pebble bed recirculation in HTGR is conducted. Velocity, FFT and correlation analyses are used to explore gas-pebble two phase flows in HTGR. Slow gas-pebble flows in HTGR have intermittent and periodic mass flow pattern. Gas-pebble interaction follows a simultaneous and linearly-dependent two-phase flow pattern. Helium-pebble flow in real HTGR is predicted to be dominated by pebble recirculation. Abstract: The pebble bed is one type of the core of the high temperature gas-cooled reactor (HTGR), which is regarded as the candidate of the generation IV advanced reactor. It is important to explore the gas-pebble flow characteristics and the pebble recirculation under the helium atmosphere. In this work, we presented a lattice Boltzmann (LB) method – immersed boundary (IB) method – discrete element method (DEM) coupled approach to simulate a test facility of pebble bed under the recirculation mode of operation. After model validation by an experiment of sphere sedimentation, the process of pebble recirculated at five constant rates are simulated. The correlations of gas motion and pebble motion in the upper and lower half beds are analyzed to uncover the inter-phase relationships for such intermittent pebble flows. Based on the systematic analyses of the two-phase flows, including the mean field and r.m.s field, the historical variation, inter-correlation, and the spectrum and phase space representations, we found sufficient evidences for the characteristics of intermittency, simultaneity, periodicity, and linear dependence for the inter-phase interaction of gas-pebble flows.